Passivity-based analysis and control of AC microgrids: Integration, operation and control of energy storage systems (2019)
Microgrids are essential subsystems of modern electric power systems. They allow providing electrical energy service for millions of people around the world by integrating multiple distributed energy resources and energy storage technologies at a small scale. This thesis studies these systems from the dynamical analysis and control point of view, to ful ll three main objectives: rst, to model pulse-width-modulated voltage and current source converters for integrating distributed energy resources in ac microgrids (Grids) with single-phase and three-phase topologies; second, to develop Hamiltonian models for representing the whole dynamics of ac Grids via classical circuit theory, since this model exhibits interconnection and dissipation structures typical in Lagrangian and Hamiltonian modeling; third, to design passivity-based controllers for guaranteeing stable operation of the entire Grids when these are operated under grid-connected or isolated modes. Hamiltonian modeling of power electronic converters based on voltage and current source technologies as well as Hamiltonian models of electrical Grids facilitate the dynamical analysis under the passivity paradigm with stability and scalability criteria. The main contributions of this thesis are: integrating supercapacitors and superconducting coils in ac power grids through a uni ed control model; uni ed ac grid modeling via circuit theory and active and reactive power decoupling in power converters under grid-connected mode as well as voltage and frequency control for isolated Grid con gurations. Finally, simulation results corroborate the theoretical developments presented in this thesis.